DTV broadcasting failover switching system using PCR information - Hyung Kim, Chang; Jeong, Seong; Hak Lee, Kyoung; Bong Sohn, Chae (International Journal of Engineering and Technology, 2018)
Background/Objectives: Major Terrestrial broadcasters, MSO (Multi-System Operator), IPTV (Internet Protocol Television) Operators have been putting effort to prevent the transmission stops such as transmission interruption.Methods/Statistical analysis: The main and spare signals of the digital broadcasting are monitored. If a problem occurs in the main signal, it automatically switched to a preliminary signal, preventing a broadcast accident before a failover switch is performed.In this paper, we propose a method that can automatically switch signal to minimize the resulting impacts on a broadcasting accident caused by a disconnection from the input or an accident from the network. Digital broadcasts transmission abides by MPEG-2 (Moving Picture Expert Group) TS (Transport Stream) standardization.Findings: This paper proposes a method to maintain the quality of broadcast such as transmission interruption within ETSI TR 101 290 (European Telecommunications Standards Institute Technical Report) standardization. Furthermore, with this proposed method, it would be possible to minimize the error from an automatically transferred stream that sent from the emergency link within ETSI TR 101 290 standardization.Improvements/Applications: A method for preventing broadcast transmission accidentsÂ Â